Using Learning Trajectories for Teacher Learning to Structure Professional Development. Issue 4 (2nd October 2017) - Bargagliotti, Anna E.; Anderson, Celia Rousseau
ABSTRACT: As a result of the increased focus on data literacy and data science across the world, there has been a large demand for professional development in statistics. However, exactly how these professional development opportunities should be structured remains an open question. The purpose of this paper is to describe the first iteration of a design experiment involving Project-SET (www.project-set.com ) professional development program. Project-SET provided professional development to enhance teachers' understanding of statistics concepts. The project constructed two learning trajectories for teacher learning and subsequently used the learning trajectories to structure the professional development curriculum. The main goal of this paper is to illustrate how the utilization of the teacher-learning trajectories to structure the professional development allowed participating teachers to develop several aspects of Statistics Knowledge for Teaching (Groth, 2013).